ANALISIS WACANA KOGNITIF PADA PEMBELAJARAN BAHASA INDONESIA MENULIS TEKS REKON - Welas; Ika Septiana (STKIP Subang, 2025)
This study is motivated by the tendency of writing instruction at the junior high school level to focus mainly on formal linguistic aspects, such as sentence structure and language errors, while paying less attention to the cognitive meaning and students’ personal experiences reflected in their texts. In fact, recount texts, as experience-based texts, are closely related to thinking processes, emotions, and the social background of the writer. This study aims to describe text structure, mental models, cognitive schemas, and social cognition represented in recount texts written by ninth-grade junior high school students on the theme of “Holiday Experiences” using Teun A. van Dijk’s cognitive discourse analysis approach. This research employed a descriptive qualitative method. The data consisted of five recount texts written by ninth-grade junior high school students. Data were collected through documentation techniques, while data analysis was conducted using cognitive discourse analysis, which includes the analysis of macrostructure, superstructure, microstructure, mental models, cognitive schemas, and social cognition based on van Dijk’s theory. The results show that all texts contain macrostructure, superstructure, and microstructure that are consistent with the characteristics of recount texts. Differences in holiday experiences influence the global meaning of the texts, language choices, and the reorientation expressed by the students. Texts describing recreational experiences tend to present positive emotional vocabulary and longer narratives, whereas texts describing routine activities display negative emotions and complaint-oriented reorientations. This study concludes that cognitive discourse analysis is effective for understanding the relationship between language, experience, and students’ cognition in writing instruction.